Views of elementary school teachers towards students with cochlear implants inclusion in the process of education - Dulčić, Adinda (Array, 2009)
Abstract: The paper reveals views of teachers in some regular elementary schools in the Republic of Croatia where students with cochlear implants, who are also rehabilitants of SUVAG Polyclinic, are educated. Survey aimed to research the views of teachers towards education. Survey included 98 teachers. Likert type scale was applied in order to identify the views of teachers towards students with hearing impairment. The survey was carried out in May 2007.Data were processed by SPSS for Windows program, version 13. Methods of descriptive statistics were applied to process frequencies of responds on variables for total sample and 3 statistically significant factors emerged by factor analysis. Results of this survey reveal that teachers have positive views towards inclusive education as a process which offers students with cochlear implants the possibility to socialize and achieve intellectual and emotional development. The survey suggests that the way of inclusion enforcement mostly satisfies the criteria specified for successful inclusion